2017
DOI: 10.3892/mmr.2017.6890
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarker analysis in patients with recurrent spontaneous abortion

Abstract: Recurrent spontaneous abortion (RSA) occurs in 1–5% of parturients. The sustained therapy and research for RSA is expensive, which is a serious issue faced by both patients and doctors. The aim of the present study was to detect protein expression profiles in the serum of RSA patients and healthy controls, and to identify potential biomarkers for this disease. A 1,000-protein microarray consisting of a combination of Human L-507 and L-493 was used. The microarray data revealed that eight serum protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…ITI-H4 and IGFBP have been reported to be associated with miscarriage [12, 13], findings similar to our results. INHBE was identified as a novel putative hepatokine with hepatic gene expression that positively correlated with insulin resistance and body mass index in humans [21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…ITI-H4 and IGFBP have been reported to be associated with miscarriage [12, 13], findings similar to our results. INHBE was identified as a novel putative hepatokine with hepatic gene expression that positively correlated with insulin resistance and body mass index in humans [21].…”
Section: Discussionsupporting
confidence: 93%
“…Some potential biomarkers for ERSA have been previously reported. Previous studies using LC–MS/MS and ELISA showed a significant decrease in the levels of insulin‑like growth factor‑binding protein‑related protein 1 (IFGBP‑rp1)/IGFBP‑7, Dickkopf‑related protein 3, the receptor for advanced glycation end products (RAGE), and angiopoietin‑2 in patients with RSA [12]. Kim et al [13] used blood samples from healthy and RPL patients to conduct a comparative proteomic study, they performed 2D-PAGE and the selected spots were analyzed with MALDI-TOF/MS.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, IGFPB7 has been recently proposed, by Wu et al. as a biomarker for the prediction and diagnosis of recurrent spontaneous abortion .…”
Section: Resultsmentioning
confidence: 99%
“…However, certain maternal characteristics, such as the age and body mass index (BMI), have shown to be very informative, with regard to the predicting miscarriage and stillbirth. The risk of preterm delivery is determined by algorithms that combine these results of the first trimester screening for aneuploidy, increased nuchal translucency, the abnormal ductus venosus flow, and low level of PAPP-A, with the characteristics of the mother [7][8][9]. Such example is the information on the length of the cervical canal from 11-to 13-week gestation [9,10].…”
Section: Early Pregnancy Screening Tests and Algorithmsmentioning
confidence: 99%